STRATEGI PENINGKATAN LIKUIDITAS DI BANK SYARIAH MANDIRI KCP PADANG PANJANG MELALUI PENAMBAHAN CUSTOMER BASE - Li Iswandi (IAIN Batusangkar, 2020)
The strategy to increase liquidity at Bank Syariah Mandiri (BSM) KCP Padang Panjang is by increasing the customer base. The purpose of this study was to see the extent of the strategy to increase liquidity at BSM KCP Padang Panjang through the addition of a customer base. This research was conducted at Bank Syariah Mandiri KCP Padang Panjang using a qualitative descriptive method. Qualitative descriptive, namely processing data by collecting more data and describing it thoroughly and in accordance with the problem being studied, so that a result of data processing will be obtained which is called research results. In this study, the type of data used is primary data, namely field data obtained directly from the people or actors who are the subjects of this study, such as through the results of interviews that have been conducted. The source of information from this study is the Branch Manager of BSM KCP Padang Panjang. Meanwhile, the secondary data sources are documents related to the problem of this research in BSM KCP Padang Panjang. The results show that liquidity problems are experienced every day by banks, both conventional and Islamic, where one of them is the unbalanced position between TPF and financing that is given every day, that is, the higher TPF that enters than the channeled financing, or vice versa.